Exploring surgeon behavioural factors impacting the quality of care: protocol for a scoping review - Megan Delisle; Nicole Askin; Bhavan Dhaliwal; Doris Goubran; Orest Fylyma; Ina Siwach; Maziar Fazel Darbandi (BMJ Open)
Introduction Modern surgery incorporates many aspects of care, including preoperative workup, surgical management and multidisciplinary collaboration to achieve favourable outcomes and high patient satisfaction. Current literature identifies variability in surgical practice and quality of care. The objective of this study is to fill the gap in the literature by identifying modifiable surgeon behavioural factors influencing the quality of care and to identify interventions and policies that modify these factors.Methods and analysis This scoping review will be reported using Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for scoping review guidelines. The protocol was drafted according to JBI Best Practice Guidance and Reporting Items for the Development of Scoping Review Protocols. A comprehensive search encompassing five databases (OVID Medline, OVID EMBASE, Cochrane Library (Central) and SCOPUS) was conducted. Search terms included ‘surgeons’, ‘surgeon characteristics’, ‘quality of care’ and ‘outcomes’ using AND, OR and ADJ2 Boolean operators. Studies describing interventions aimed at modifying behavioural surgeon factors influencing the quality of healthcare will be included. Studies describing institutional or system factors will be excluded. Searches were limited from 1 January 2000 to 1 January 2024 to capture modern surgery practices. Searches were peer reviewed as per Peer Review of Electronic Search Strategies 2015. Two independent reviewers will perform a title and abstract screening using DistillerSR and extract data on the participants, study methods, modifiable surgeon factors and interventions that modify these factors. The data will be qualitatively analysed using the COM-B Framework which describes how capability, motivation and opportunity constitute behaviour. We expect to compile a list of existing interventions aimed at modifying surgeon behaviours, analysing the success of existing interventions to improve patient outcomes and identifying modifiable surgeon factors that do not have interventions.Ethics and dissemination Ethics approval and patient consent are not required. The results will be submitted to a peer-reviewed journal for publication.